Stakeholder engagement in developing a father-inclusive early life obesity prevention intervention: First Heroes - Santana R. Silver; Rachel C. Whooten; Gracia M. Kwete; Haley Farrar-Muir; Rachel N. Cournoyer; Elizabeth A. Barth; Milton Kotelchuck; Elsie M. Taveras (BMC, 2022)
Abstract Background Although paternal involvement in the perinatal period is associated with benefits for maternal-child health and reduced obesity risk, fathers are seldom included in perinatal or obesity prevention efforts. Engaging community leaders and fathers as stakeholders in intervention development is a critical step in designing a father-inclusive intervention that is efficacious and responsive to their needs. Methods We conducted a structured engagement study, including community stakeholder engagement and qualitative interviews with new fathers, to inform the development of a prospective randomized controlled trial that includes mothers and fathers as equal partners in infant obesity prevention. We interpreted stakeholder feedback through the Consolidated Framework for Implementation Research (CFIR) framework. Results Between September 2019 and April 2020, we held a Community Engagement meeting, formed a Community Advisory Board, and conducted 16 qualitative interviews with new fathers. Stakeholder engagement revealed insights across CFIR domains including intervention characteristics (relative advantage, complexity, design quality & packaging), outer setting factors (cosmopolitanism and culture), individual characteristics (including self-efficacy, state of change, identification with the organization) and process (engagement and adaptation). Stakeholders discussed the diverse challenges and rewards of fatherhood, as well as the intrinsic paternal motivation to be a loving, supportive father and partner. Both community leaders and fathers emphasized the importance of tailoring program delivery and content to meet specific parental needs, including a focus on the social-emotional needs of new parents. Conclusions A structured process of multidimensional stakeholder engagement was successful in improving the design of a father-inclusive perinatal obesity prevention interventions. Father engagement was instrumental in both reinforcing community ties and increasing our understanding of fathers' needs, resulting in improvements to program values, delivery strategies, personnel, and content. This study provides a practical approach for investigators looking to involve key stakeholders in the pre-implementation phase of intervention development. Trial registration ClinicalTrials.gov, NCT04477577 . Registered 20 July 2020.